Pengaruh Kinerja Lingkungan, Intesitas Modal dan Ukuran Perusahaan Terhadap Pengungkapan Informasi Lingkungan - Ardana, Ari Bawa; Werastuti, Desak Nyoman Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to determine the Effect Of Environmental Performance, Capital Intensity, And Company Size On The Disclosure Of Environmental Information Of Manufacturing Companies listing on the Indonesia Stock Exchange in 2017-2019 and conducting empirical studies on the sustainability report of Manufacturing companies to determine the effectiveness of social and environmental disclosure based on the Global Reporting Initiative G4 through the three dependent variables. The design used in this study is quantitative research. The number of samples is 50 companies selected through purposive sampling techniques with a total of 150 samples from 3 years of observation. Data analysis methods used are multiple regression analysis and data presentation assisted with the Statistical Package for Social Science (SPSS) 23.0 programs for windows. The results showed that environmental performance, capital intensity and company size has a positive effect on disclosure of corporate environmental information